Combined physical training protects the left ventricle from structural and functional damages in experimental pulmonary arterial hypertension - Luciano Bernardes Leite; Leôncio Lopes Soares; Alexandre Martins Oliveira Portes; Thayana Inácia Soares; Bruna Aparecida Fonseca da Silva; Taís Rodrigues Dias; Sebastião Felipe Ferreira Costa; Luiz Otávio Guimarães-Ervilha; Mirian Quintão Assis; Victor Neiva Lavorato; Albená Nunes da Silva; Mariana Machado-Neves; et al. (BMC, 2024)
Abstract Background Under the adverse remodeling of the right ventricle and interventricular septum in pulmonary arterial hypertension (PAH) the left ventricle (LV) dynamics is impaired. Despite the benefits of combined aerobic and resistance physical trainings to individuals with PAH, its impact on the LV is not fully understood. Objective To test whether moderate-intensity combined physical training performed during the development of PAH induced by MCT in rats is beneficial to the LV's structure and function. Methods Male Wistar rats were divided into two groups: Sedentary Hypertensive Survival (SHS, n = 7); and Exercise Hypertensive Survival (EHS, n = 7) to test survival. To investigate the effects of combined physical training, another group of rats were divided into three groups: Sedentary Control (SC, n = 7); Sedentary Hypertensive (SH, n = 7); and Exercise Hypertensive (EH, n = 7). PAH was induced through an intraperitoneal injection of MCT (60 mg/kg). Echocardiographic evaluations were conducted on the 22nd day after MCT administration. Animals in the EHS and EH groups participated in a combined physical training program, alternating aerobic (treadmill running: 50 min, 60% maximum running speed) and resistance (ladder climbing: 15 climbs with 1 min interval, 60% maximum carrying load) exercises, one session/day, 5 days/week for approximately 4 weeks. Results The physical training increased survival and tolerance to aerobic (i.e., maximum running speed) and resistance (i.e., maximum carrying load) exertions and prevented reductions in ejection fraction and fractional shortening. In addition, the physical training mitigated oxidative stress (i.e., CAT, SOD and MDA) and inhibited adverse LV remodeling (i.e., Collagen, extracellular matrix, and cell dimensions). Moreover, the physical training preserved the amplitude and velocity of contraction and hindered the reductions in the amplitude and velocity of the intracellular Ca2+ transient in LV single myocytes. Conclusion Moderate-intensity combined physical training performed during the development of MCT-induced PAH in rats protects their LV from damages to its structure and function and hence increases their tolerance to physical exertion and prolongs their survival.